The Chinese Gazette in European Sources from the Late Qianlong Period: The Case of the Siku Quanshu. - Standaert, Nicolas (T'oung Pao, 2021)
The publicly available government gazette (often called dibao 邸報) that was published in a variety of formats in imperial China has recently caught new academic interest both in China and in the West. While most of these studies focus on the Peking Gazette (jingbao 京報) in the (late) nineteenth century, information about the gazette for earlier times remains very scarce. To address this gap, the present study focuses on the gazette from the Qianlong period (1736–1795). It uses and describes both Chinese sources, specifically the tizou shijian 題奏事件, and European sources, especially the French translations of gazettes by Jean-Joseph-Marie Amiot (1718–1793). A case study of translated reports on the Siku quanshu 四庫全書 sent to Europe shows how the Chinese gazette became part of a remarkable and lively global information network. Résumé: Le journal officiel du gouvernement (souvent appelé dibao 邸報), publié dans divers formats en Chine impériale, a récemment suscité un nouvel intérêt académique tant en Chine qu' en Occident. Si la plupart de ces études portent sur la Gazette de Pékin (jingbao 京報) à la (fin) du XIXe siècle, les informations sur la gazette des temps anciens restent très rares. Pour combler cette lacune, la présente étude se concentre sur la gazette de la période Qianlong (1736–1795). Elle utilise et décrit à la fois des sources chinoises, en particulier le tizou shijian 題奏事件, et des sources européennes, notamment les traductions françaises des gazettes de Jean-Joseph-Marie Amiot (1718–1793). Une étude de cas sur les rapports traduits au sujet du Siku quanshu 四庫全書 envoyés en Europe montre comment la gazette chinoise s' est intégrée à un remarquable et vivant réseau mondial d' information. 摘要: 帝國時期版式多樣且公開流布的政府公報（又常被稱為邸報）最近再次引起了中西學界的研究興趣。此類研究的重心主要集中於十九世紀（晚期）的《京報》，對更為早期的公報則不置一詞。旨在彌補這方面的缺憾，本文就乾隆時期（1736–1795）的政府公報展開討論，並對以下兩種史料進行具體分析和描述：取自清朝的《題奏事件》和取自歐洲、傳教士錢德明（Jean-Joseph-Marie Amiot, 1718–1793）的法語譯本。通過一個個案研究，本文將展示涉及《四庫全書》的相關公告在被翻譯和寄往歐洲之後，如何構成了當時頗為活躍的全球信息網絡的一部分。